CULTURE AND EDUCATION - Edward Sitepu; A Dan Kia (SAINT PAUL'S REVIEW, 2021)
Aspects of culture and education should be complementary in terms of complementing and reinforcing each other. Both are real and research results in various countries show the presence and potential of efforts to bridge the two possible. The influence of capable technology in the learning process requires transformation and it is directly related to educators who understand the student process. From among the institutions as the organizers apply to be adaptive to change. The connotation of being able to adapt to the rapid and complex flow of change. This article tries to answer this real problem.